2007
DOI: 10.1007/s00256-007-0319-1
|View full text |Cite
|
Sign up to set email alerts
|

The healing pattern of osteoid osteomas on computed tomography and magnetic resonance imaging after thermocoagulation

Abstract: Objective To compare the healing pattern of osteoid osteomas on computed tomography (CT) and magnetic resonance imaging (MRI) after successful and unsuccessful thermocoagulation. Materials and methods Eighty-six patients were examined by CT and 18 patients by dynamic gadolinium-enhanced MRI before and after thermocoagulation for osteoid osteoma. Thermocoagulation was successful in 73% (63/86) and unsuccessful in 27% (23/86) of patients followed by CT. Thermocoagulation was successful in 72% (13/18) of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
19
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 18 publications
6
19
1
1
Order By: Relevance
“…Thus, neither pre-or postprocedural nidus size nor location or nidus morphology should influence the therapy decision-making or be used as an outcome predictor. This result is supported by the data of Vanderschueren et al (37), who found that the nidus size was not correlated with unsuccessful coagulation. PostRFA MRI changes that are supposed to indicate healing (decrease in contrast enhancement, diminished/ vanished edema) were accompanied by a marked reduction in the VAS pain score.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Thus, neither pre-or postprocedural nidus size nor location or nidus morphology should influence the therapy decision-making or be used as an outcome predictor. This result is supported by the data of Vanderschueren et al (37), who found that the nidus size was not correlated with unsuccessful coagulation. PostRFA MRI changes that are supposed to indicate healing (decrease in contrast enhancement, diminished/ vanished edema) were accompanied by a marked reduction in the VAS pain score.…”
Section: Discussionsupporting
confidence: 82%
“…To prove this hypothesis, a prospective study with a quantitative assessment of the enhancement and the inclusion of relapsed patients would be desirable. However, our findings show that even a persistence of those signs of potential activity (edema, contrast enhancement) are not necessarily correlated with the clinical symptoms, thus supporting the previous findings of Vanderschueren et al (37), who described a persistent "edema-like" pattern in 5/5 unsuccessfully treated patients and also in 9/13 successfully treated patients.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…3). Brodie's abscess may be morphologically indistinguishable from a nidus in MR [8] as well as in CT images [5,6,16,18,19]. In our experience, the contrast enhancement in chronic osteomyelitis increases more gradually than in osteoid osteomas and shows no clear-cut decrease (wash-out effect) in the late phase.…”
Section: Discussionmentioning
confidence: 53%
“…As open surgery has been increasingly replaced by minimally invasive procedures and as the lesion may also be treated with prostaglandin E2 inhibitors, a histological confirmation is usually not obtained. Therefore, diagnosis depends entirely on radiological imaging [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%